Outcomes of implant-based oral rehabilitation in head and neck oncology patients-a retrospective evaluation of a large, single regional service cohort - Dominic P. Laverty; Owen Addison; Berhanu A. Wubie; Giseon Heo; Sat Parmar; Timothy Martin; Prav Praveen; David Pearson; David Newsum; Michael Murphy; Geoffrey Bateman (SpringerOpen, 2019)
Abstract Background The study reports on implant survival outcomes in head and neck cancer patients who received implant-based oral rehabilitation in a regional service centre. Methods A retrospective analysis of implant survival outcomes in patients treated in a regional service from 2012 to 2017 was performed. The primary outcome measure was implant survival. The secondary outcome measure was to assess the effect of covariates associated with implant failure including bone type, radiotherapy, chemotherapy, gender and surgical implant complications. Kaplan-Meier survival curves were applied to compare differences in the survival rates of groups of variables. Cox proportional hazards models were applied to identify covariates associated with implant failure. p value was set at 0.05. Results The sample was composed of 167 head and neck cancer patients who had 779 dental implants placed. Implant survival estimates were calculated: 3 years, 95.7% [95%CI 94.3-97.2%] and 5 years, 95.5% [95%CI 93.9-97.0%], with a median follow-up of 38 months. Gender (p = 0.09), radiotherapy (p = 0.16) and chemotherapy (p = 0.17) did not significantly influence implant survival, whereas implant failure was higher in transported (reconstructed) bone sites in comparison with native bone (p < 0.01). Conclusion The result of this study suggests that overall implant survival as part of the routine oral rehabilitation is high in this patient cohort; however, implant failure was found to be statistically higher for implant placed into transported bone in comparison to native bone.